Les métiers du fromage dans la peinture alpine à la fin du Moyen Âge : production et réception d’images du travail paysan - Marianne Cailloux (Images du Travail, Travail des Images)
A lot of wall paintings demonstrates a complex representation of work during the Late Medieval and the Early Modern periods in Occidental Europe. In the Western Alps, sacred and secular images use the agricultural professional world as a “background” scenery, a lively landscape to help anchor the extraordinary lives of famous characters (like saints and elders) within the day-to-day reality. Various Piemontese examples allow one to analyse how the Quattrocento painters represent work – for example the characteristic Alpine cheesemongers. These images picture a form of specialisation from the artists with a precise knowledge of professional techniques and a shared alpine culture with their commissioners. Through legend or sanctification, the depictions illustrate finally an appreciation of the worker and their tasks, reaching a socio-political dimension and defining a certain idea of what work was supposed to be at that time.